Destino de los créditos productivos otorgados por la cooperativa de ahorro y crédito de la pequeña empresa Cacpe Zamora Ltda., y su incidencia en el desarrollo socioeconómico de sus clientes periodo 2010 - 2013 - Herrera Caraguay, Zoila Katherine (2015)
The persistent development of the cooperative system of savings and credit as suppliers in the domestic financial market, and in particularly, in the canton Zamora has influenced certain economic activities and in socio-economic development of the canton’s habitants. The credit union small business CACPE- Zamora has been operating since 1989 and contributing significantly in the financial market of the province. For that reason it has been decided to conduct an investigation entitled "Destination of productive loans from the Cooperative Credit Union small business CACPE Zamora Ltda, and their impact on the socioeconomic development of its customers between 2010-2013". The main objective of the research was to determine the extent, distribution and types of productive loans granted by the CACPEZ and its relation to the improvement of the socioeconomic situation of their clients. The research was conducted in the canton Zamora and was based on the scientific method and its expressions such as inductive, deductive, analytical, synthetic. In turn, the techniques of literature review, interview and survey index card with their instruments, questionnaire and interview guide and questionnaire with closed and multiple alternative same questions was submitted to the implementation of a pilot test in order to gather was used primary relevant and reliable information to fulfill the objects stated above. The object study population was 7791 customers who have made credits, we worked with a representative sample of 366 surveys and an interview addressed to General Manager and to the Head of Credit Department of the institution interviews. After analyzing the results of the information gathering was concluded that in the canton Zamora loans were mainly for farming and trade and agricultural activities in the short term, directly influencing the economic development of its members. The main reason is that the financial institution provides access credit to the productive sector, boosting own productive activities canton having the necessary liquidity and solvency. In addition it is concluded that the loans granted by the CACPEZ Cooperative contributes significantly obtaining an improvement of their income that allows them to improve their standard of living. KEYWORDS: productive activities, credits, socioeconomic.